"Membangun Kesadaran Digital Finansial: Edukasi Literasi Keuangan untuk Mencegah Judi Online di Remaja Pedesaan di Desa Terak" - Muhammad Faisal Akbar; Ariandi A Zulkarnain; Rahmat Robuwan (Indonesian Journal of Dedication and Educations, 2026)
The Integrated Student Service Program of the University of Bangka Belitung (PMTU) with the theme “Building Digital Financial Awareness: Financial Literacy Education to Prevent Online Gambling among Rural Youth” in Terak Village was implemented as an effort to build awareness and resilience among adolescents against the dangers of online gambling through the enhancement of financial and digital literacy. This program responds to the low understanding of rural communities regarding financial management, digital transaction risks, and the social impacts of online gambling. Through educational approaches and direct socialization, the activity successfully improved participants’ understanding of basic financial planning, distinguishing needs and wants, managing online loan risks, and recognizing the legal consequences of digital gambling. The program’s tangible impacts are reflected in three main aspects: the increase in knowledge and ability to map personal budgets, the development of positive attitudes and commitment to reject gambling invitations, and the establishment of an Anti-Gambling Community as a platform for program sustainability. This educational intervention serves as a strategic step to strengthen digital financial awareness among rural youth while supporting the development of a productive and responsible young generation in the digital era.